18 Surface binding followed by Ca2+ influx results in selective activation of human regulatory T cells (Treg) by tumor-derived exosomes (TEX). Issue 5 (May 2015) - Muller, L.; Simms, P.; Nishimura, M.; Watkins, S.; Whiteside, T.
Abstract : Ca2+ signals are critical for T-cell function, and Ca2+ influx is an early event in T-cell activation. TEX, ubiquitously present in the tumor microenvironment and plasma, carry a cargo of suppressive and stimulatory molecules. TEX bind to the surface of immune cells, suppressing functions of some T cells while up-regulating functions of others. To determine whether binding of TEX or exosomes produced by normal cells (EXO) to primary T cells results in delivery of signals regulating activation, human PBMC or different freshly-isolated T-cell subsets were co-incubated with PKH-26 labeled exosomes isolated from normal or HNSCC plasma specimens and from supernatants of HNSCC cell lines as described by us (Muller et al., J. Immunol. Methods, 2014). CD4+ T cell, CD8+ T cell and CD4 + CD39+ Treg were isolated from normal PBMC using AutoMACS. Binding of PKH-26-labeled TEX or EXO by T cells, NK cells or monocytes was evaluated following co-incubation for 24–96 h using an AMNIS image cytometer. The strength of Ca2+ influx induced by TEX or EXO in various T cells was measured by confocal microscopy after staining the T cells with a Fura-2 or Fluo-4 dye. AMNIS flow data showed that binding of TEX and EXO to T cells was time and dose-dependent, but exosomes were not internalized even after prolonged [96 h] co-incubation. Ca2+ influx was time dependent and was observed only after co-incubation of T cells with TEX but not (or only minimally) with EXO. Among T cells, CD4 + CD39+ Treg were preferentially targeted by TEX, showing the strongest Ca2+ influx within 30 min. In AMNIS, TEX binding to Treg gave a significantly stronger signal than that measured with CD4+ or CD8+ T cells. This strong, sustained Ca2+ influx induced in Treg by TEX is consistent with our previous functional data demonstrating selective TEX-mediated Treg activation and proliferation. The data also emphasizes the fact that activation of Treg functions by TEX is regulated through signals delivered to the Treg surface and does not require exosome up-take or their internalization by the target cells.